PENERAPAN STRATEGI PEMASARAN PADA UMKM DESA TELUK SASAH (STUDI KASUS PADA KUBE KENANGA) - Anggia Sekar Putri; Yuritanto, Yuritanto; Yusrizal, Yusrizal; Alfi Hendri; Maryati, Maryati; Marsudi, Marsudi; Raja Hardiansyah (JURNAL PENGABDIAN MANDIRI, 2025)
Service activities through Discussions with MSMEs and Brand Identity Creation which were initiated by KKN students from STIE Pembangunan Tanjungpinang are one solution to increase the understanding of MSME actors regarding various marketing strategies that can be applied in their businesses. By providing a better understanding of modern marketing techniques, this program aims to help MSMEs identify and exploit existing market opportunities. Apart from that, this program also aims to build a network between MSME players who can support each other in business development. The targets for this program are members of Kube Kenaga, Teluk Sasah Village. Based on the observations made, this discussion activity was carried out well and was attended by 8 members of the kube ylang. Participants gave positive responses by actively conducting questions and answers to STIE Pembangunan Tanjungpinang students. Brand identity creation activities also received a good response from MSME players, because a consistent identity can increase customer confidence in the products offered.